2022
DOI: 10.1007/s00431-021-04338-y
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in pediatric cancer: a systematic review

Abstract: The outbreak of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in December 2019 in Wuhan challenges pediatric oncologists in an unexpected way. We provide a comprehensive overview, which systematically summarizes and grades evidence (QoE) on SARS-CoV-2 infections in pediatric cancer patients at 1.5 years of pandemic. A systematic literature search in PubMed combined with an additional exploratory literature review in other international databases was conducted to identify studies on chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 57 publications
5
32
0
2
Order By: Relevance
“…13 A systematic review by Schlage, et al on COVID-19 and pediatric cancer reported that COVID-19 infection in pediatric cancer patients resulted in severe disease in only a minority of patients; however, despite a milder course, mortality rate was higher than in children with no comorbidities, with deaths attributable to either COVID-19 complications or cancer progression. 20 In another study by Williams, et al, cardiac comorbidities were most common in children with severe and critical COVID-19. 21 Among MIS-C cases, obesity was the most common comorbidity, consistent with the report of Hoste, et al 16 With obesity being associated with a chronic subclinical inflammatory status, it is hypothesized that COVID-19 infection triggers a greater hyperinflammatory response and higher endothelial, macrophage and adipocyte activation, leading to considerably elevated inflammatory markers and more severe complications.…”
Section: Resultsmentioning
confidence: 97%
“…13 A systematic review by Schlage, et al on COVID-19 and pediatric cancer reported that COVID-19 infection in pediatric cancer patients resulted in severe disease in only a minority of patients; however, despite a milder course, mortality rate was higher than in children with no comorbidities, with deaths attributable to either COVID-19 complications or cancer progression. 20 In another study by Williams, et al, cardiac comorbidities were most common in children with severe and critical COVID-19. 21 Among MIS-C cases, obesity was the most common comorbidity, consistent with the report of Hoste, et al 16 With obesity being associated with a chronic subclinical inflammatory status, it is hypothesized that COVID-19 infection triggers a greater hyperinflammatory response and higher endothelial, macrophage and adipocyte activation, leading to considerably elevated inflammatory markers and more severe complications.…”
Section: Resultsmentioning
confidence: 97%
“…In the Abi Vijenthira study, adult patients with hematologic malignancy and COVID-19 had a 34% risk of death, whereas pediatric patients had a 4% risk of death [ 5 ]. In a systematic review by Schlage and colleagues about COVID-19 in pediatric cancer comprising over 1000 patients, the attributable mortality was at least 10 times higher compared to the reports on hospitalized children without comorbidities [ 2 ]. Published data from our center regarding COVID-19 mortality was reported to be 15% while in the current study, CAPFI was associated with higher mortality rate among pediatric cancer patients as failure was reported in 38% of patients, with 20% of patients’ deaths attributable to CAPA [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic has markedly affected pediatric cancer patients. Children with malignancies were assumed to be at higher risk for severe coronavirus disease 2019 (COVID-19) due to their immunocompromised state; however, many studies reported that most pediatric cancer patients experience only mild to moderate COVID-19 infection [ 1 , 2 , 3 ]. Among patients with confirmed COVID-19, the frequency of cancer diagnosis has been reported to be 2% [ 4 ], with a 34% mortality risk rate [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of all these various treatments in hematology patients deserves further studies. The drug availability in each country and the expertise of infectious disease experts should be considered when determining the treatment for pediatric AML with COVID19 [52][53][54].…”
Section: Anti-viral Prophylaxismentioning
confidence: 99%